Out‐of‐Hospital Cardiac Arrest in Patients With and Without Psychiatric Disorders: Differences in Use of Coronary Angiography, Coronary Revascularization, and Implantable Cardioverter‐Defibrillator and Survival. Issue 16 (20th August 2019) - Barcella, Carlo Alberto; Mohr, Grimur Høgnason; Kragholm, Kristian Hay; Gerds, Thomas Alexander; Jensen, Svend Eggert; Polcwiartek, Christoffer; Wissenberg, Mads; Lippert, Freddy Knudsen; Torp‐Pedersen, Christian; Kessing, Lars Vedel; Gislason, Gunnar Hilmar; Søndergaard, Kathrine Bach
Abstract : Background: Healthcare disparities for psychiatric patients are common. Whether these inequalities apply to postresuscitation management in out‐of‐hospital cardiac arrest (OHCA) is unknown. We investigated differences in in‐hospital cardiovascular procedures following OHCA between patients with and without psychiatric disorders. Methods and Results: Using the Danish nationwide registries, we identified patients admitted to the hospital following OHCA of presumed cardiac cause (2001‐2015). Psychiatric disorders were identified using hospital diagnoses or redeemed prescriptions for psychotropic drugs. We calculated age‐ and sex‐standardized incidence rates and incidence rate ratios (IRRs) of cardiovascular procedures during post‐OHCA admission in patients with and without psychiatric disorders. Differences in 30‐day and 1‐year survival were assessed by multivariable logistic regression in the overall population and among 2‐day survivors who received acute coronary angiography (CAG). We included 7288 hospitalized patients who had experienced an OHCA: 1661 (22.8%) had a psychiatric disorder. Compared with patients without psychiatric disorders, patients with psychiatric disorders had lower standardized incidence rates for acute CAG (≤1 day post‐OHCA) (IRR, 0.51; 95% CI, 0.45–0.57), subacute CAG (2–30 days post‐OHCA) (IRR, 0.40; 95% CI, 0.30–0.52), and implantable cardioverter‐defibrillator implantation (IRR, 0.67; 95% CI, 0.48–0.95). Conversely, we did not detect differences in coronary revascularization among patients undergoing CAG (IRR, 1.11; 95% CI, 0.94–1.30). Patients with psychiatric disorders had lower survival even among 2‐day survivors who received acute CAG: (odds ratio of 30‐day survival, 0.68; 95% CI, 0.52–0.91; and 1‐year survival, 0.66; 95% CI, 0.50–0.88). Conclusions: Psychiatric patients had a lower probability of receiving post‐OHCA CAG and implantable cardioverter‐defibrillator implantation compared with nonpsychiatric patients but the same probability of coronary revascularization among patients undergoing CAG. However, their survival was lower irrespective of angiographic procedures.